Monomorphic Ventricular Tachycardia during the Insertion of the Nasogastric Tube via the Nasal Route - Sharath Krishnaswami; Dheeraj Masapu; Satish Rudrappa (Journal of Medical Sciences and Health)
Naso gastric tubes are used to administer medications or nutrition in patients who have a functional gastrointestinal tract but are unable to tolerate oral intake. Cardiac arrhythmias like asystole, and polymorphic ventricular tachycardia have been seen, but they remain rare complications of Nasogastric tube insertion. Here, we bring to you a case of Intracranial Haemorrhage post craniotomy and evacuation of hematoma who developed monomorphic ventricular tachycardia during the insertion of the nasogastric tube via the nasal route.